NEW DIGITAL TECHNOLOGIES: CHALLENGES AND OPPORTUNITIES: NEW DIGITAL TECHNOLOGIES: CHALLENGES AND OPPORTUNITIES - Yordanov, Nikolay; Yankova-Yordanova, Yordanka (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
This text explores the nature, applications, and challenges of new digital technologies as a key driver of transformation in the modern economy and society. The first chapter defines the concept of “digital technologies” and presents the main technological domains-artificial intelligence, big data, the internet of things, cloud computing, blockchain, and digital twins. Their core characteristics, such as scalability, network effects, and data-driven models, are highlighted. The second chapter analyzes the application of digital technologies across different sectors-services, healthcare, and education-showing how they stimulate innovation, productivity, and competitiveness. The discussion also covers the broader socio-economic effects, including changes in the labor market and skills, digital inequality, and the digitalization of public services. The third chapter outlines the main challenges of digital transformation: technological integration, lack of standardized frameworks, digital divides, and ethical and security concerns. Future research directions are identified, focusing on multi-level analysis, sustainability, measurement and methodological development, and the inclusion of small and medium-sized enterprises and developing economies.